KAŞİF DİVANI`NIN TENKİTLİ METNİ VE TAHLİLİ - BÜYÜKYILDIRIM, AYŞE (Fırat Üniveristesi, 1998)
[Abstract Not Available]
The critical text and the analysis of the Divan of Kaşif
Keywords: Türk Dili ve Edebiyatı; Turkish Language and Literature